2006
DOI: 10.1111/j.1745-7599.2006.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity: Prevention practices of nurse practitioners

Abstract: Although the majority of the NPs in this study reported being aware of childhood obesity prevention guidelines (73.7%), most were not consistently using BMI for age or monitoring children at increased risk for obesity. Because childhood obesity is escalating at such a rapid rate, it is critical that NPs working in family practice and pediatric practice settings take the necessary steps to help curtail obesity in childhood, including calculating BMI for age, targeting children at risk, and helping families deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 30 publications
2
52
0
2
Order By: Relevance
“…24,26,28 Young et al 23 recommend consistent identification and treatment of overweight and obesity as the standard of care for all children admitted to children' s hospitals. This is the first study to specifically examine recognition, diagnosis, and treatment of overweight and obesity in children hospitalized for asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,26,28 Young et al 23 recommend consistent identification and treatment of overweight and obesity as the standard of care for all children admitted to children' s hospitals. This is the first study to specifically examine recognition, diagnosis, and treatment of overweight and obesity in children hospitalized for asthma.…”
Section: Discussionmentioning
confidence: 99%
“…21 Identifying, plotting, and monitoring BMI percentile are essential steps in the algorithm 22 and are recommended for all hospitalized children by the National Association of Children' s Hospitals and Related Institutions, 23 but studies have shown that providers in both primary care and inpatient settings are failing to measure and monitor BMI percentile. [24][25][26] A recent study by King et al 27 described lack of identification and treatment of overweight and obesity in hospitalized children; however, only a small number of patients with asthma were included, and results specific to the patients with asthma were not described.…”
mentioning
confidence: 99%
“…Advanced practice nurses (APNs) are integral to providing lifestyle interventions for many chronic and complex health conditions including obesity (Parkinson & Parker, 2013). Nurse practitioners who integrate prevention strategies into their practice may help to alleviate the problem of adolescent obesity (Larsen, Mandleco, Williams, & Tiedeman, 2006).…”
Section: Background and Significancementioning
confidence: 99%
“…Evidence is beginning to support that weight gain in early life, including infancy, is a predictor of later obesity and that lifestyle behaviors have their roots in early childhood (Rudolf et al ,201 0). Furthermore, Larsen, Mandleco, Williams, and Tiedeman (2006) state that once a child becomes overweight treatment to decrease weight is difficult and often unsuccessful. Hence, the early years are considered to be a key time for developing both an unhealthy weight and its precursor behaviors (Campbell & Hesketh, 2007;Legislative Assembly of British Columbia, 2006).…”
Section: Demography Of Childhood Obesitymentioning
confidence: 99%
“…Moreover, Larsen et al (2006) acknowledge that NPs are not exempt from this inadequacy in educational need. They utilized a convenience sample of 99 family and pediatric NPs from Texas to evaluate common NP pediatric obesity prevention practices.…”
Section: Barriers To Obesity Managementmentioning
confidence: 99%